Mind the Gap Tracing the Origins of Human Universals - Kappeler, Peter M.; Silk, Joan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
What makes us human? What made us become the way we are? One way to answer these questions is to identify the traits that all humans share, traits that are universal features of all human societies. Another way to do so is to ask how humans differ from other species, particularly from our closest relatives, the nonhuman primates. The contributors to this book pursue both approaches, in an effort to understand how evolution has shaped modern human behavior and societies.
Primate Behavior and Human Universals: Exploring the Gap -- Family & Social Organization -- The Deep Structure of Human Society: Primate Origins and Evolution -- Conflict and Bonding Between the Sexes -- The Unusual Women of Mpimbwe: Why Sex Differences in Humans are not Universal -- Politics & Power -- Dominance, Power, and Politics in Nonhuman and Human Primates -- Human Power and Prestige Systems -- The End of the Republic -- Intergroup Relationships -- Intergroup Aggression in Primates and Humans: The Case for a Unified Theory -- Why War? Motivations for Fighting in the Human State of Nature -- Foundations of Cooperation -- From Grooming to Giving Blood: The Origins of Human Altruism -- Evolved Irrationality? Equity and the Origins of Human Economic Behavior -- From Whence the Captains of Our Lives: Ultimate and Phylogenetic Perspectives on Emotions in Humans and Other Primates -- Language, Thought & Communication -- Primate Communication and Human Language: Continuities and Discontinuities -- Language, Lies and Lipstick: A Speculative Reconstruction of the African Middle Stone Age (3z(BHuman Revolution(3y (B-- Brain and Behaviour in Primate Evolution -- The Gap is Social: Human Shared Intentionality and Culture -- The Evolution and Development of Human Social Cognition -- Deceit and Self-Deception -- Human Universals and Primate Symplesiomorphies: Establishing the Lemur Baseline -- Innovation & Culture -- Ape Behavior and the Origins of Human Culture -- The Coevolution of Genes, Innovation, and Culture in Human Evolution -- Conclusions -- Mind the Gap: Cooperative Breeding and the Evolution of Our Unique Features.s
Keywords: Life sciences; Animal behavior; Evolution (Biology).; Zoology; Anthropology; Developmental psychology; Consciousness; Life Sciences; Behavioural Sciences; Evolutionary Biology; Developmental Psychology; Cognitive Psychology; Anthropology; Zoology